How family and child cash transfers can empower women: Comparative lessons from Brazil and South Africa. (August 2021) - Hunter, Wendy; Patel, Leila; Sugiyama, Natasha Borges
By leveraging a comparison of Brazil's Bolsa Família and South Africa's Child Support Grant, this article probes whether and how income transfer programs enhance the standing of women recipients. Empowerment is assessed according to economic decision making, bodily protection and integrity, and psycho-social wellbeing and growth. The comparative analysis determines that regular income assistance boosts the self-esteem and agency of women recipients in both countries. At the same time, it underscores the heightened benefits obtained in Brazil as a result of the cash transfer program being embedded in a stronger public health and social service network. That Bolsa recipients interact with these associated institutions generates multiple downstream benefits. The broader lesson is that income transfer programs need to operate in deliberate coordination with an array of ancillary social service institutions to deliver the maximum benefits for women's empowerment.